Enhancing Accessibility through Inclusive Design and Artificial Intelligence: A Comprehensive Analysis Based on WCAG Guidelines - Anand Sarangam (North American Journal of Engineering Research, 2024)
The evaluation of artificial intelligence (AI) in enhancing digital accessibility and compliance with WCAG, Section 508 and EN 301 standards. How AI technology can provide greater access to digital content for individuals with disabilities using features like screen readers, automatic captioning and image recognition. The study also examines emerging issues of concern such as the issue of biased algorithms, privacy and the problem of having human interventions for AI systems. The work examines the contemporary AI technologies and their applied implications for digital accessibility thereby informing the reader on the potential steps and innovation in making the digital space more open for everyone.